Philosophy of music : a history - Martinelli, Riccardo, 1964- (De Gruyter, 2019)
Ranging from Antiquity to contemporary analytic philosophy, it provides a concise but thorough analysis of the arguments developed by some of the most outstanding philosophers of all times. Besides the aesthetics of music proper, the volume touches upon metaphysics, ethics, philosophy of language, psychology, anthropology, and scientific developments that have influenced the philosophical explanations of music. Starting from the very origins of philosophy in Western thought (Pythagoras, Plato, Aristotle) the book talks about what music is according to Augustine, Descartes, Leibniz, Rousseau, Kant, Hegel, the Romantics, Schopenhauer, Nietzsche, Wittgenstein, Susanne Langer, Bloch, Adorno, and many others. Recent developments within the analytic tradition are illustrated with particular attention to the ontology of the musical artwork and to the problem of music and emotions. A fascinating idea which recurs throughout the book is that philosophers allow for a sort of a secret kinship between music and philosophy, as means to reveal complementary aspects of truth.